Determinants of Stock Returns: The Role of Ownership Structure, Firm Fundamentals, and Market Variables in Sharia Stocks - Lela Hindasah (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study aims to examine the effect of ownership structure (institutional ownership, managerial ownership, and foreign ownership), firm fundamentals (profitability, leverage, dividend policy, and firm size), and market variables (book-to-market ratio, trading volume, and stock volatility) on the stock returns of Sharia-compliant firms listed on the Indonesia Stock Exchange during the 2020 pandemic crisis. The study utilizes a sample of 322 Sharia-compliant firms in 2020 and employs multiple linear regression analysis. The results indicate that managerial ownership and institutional ownership do not have a significant effect on stock returns, while foreign ownership has a negative effect. Regarding firm fundamentals, Return on Assets (ROA) and market capitalization have a positive effect on stock returns, whereas leverage and dividend policy do not show significant influence. Among market variables, the book-to-market ratio has a positive effect on stock returns, while trading volume and stock volatility are found to be insignificant. These findings suggest that during a crisis period, firm fundamentals and stock valuation remain the primary determinants influencing investment decisions in the Sharia stock market.